Budget impact of ferric carboxymaltose treatment in patients with chronic heart failure and iron deficiency in Spain. (1st December 2020) - Delgado, Juan F.; Oliva, Juan; González-Franco, Álvaro; Cepeda, Jose María; García-García, Jose Ángel; González-Domínguez, Almudena; Garcia-Casanovas, Albert; Jiménez Merino, Silvia; Comín-Colet, Josep
Abstract: Objective: The treatment of iron deficiency (ID) with ferric carboxymaltose (FCM) improves the functional class and quality of life of chronic heart failure (CHF) patients with reduced left ventricular ejection fraction (LVEF), and reduces the rate of hospitalization due to worsening CHF. This study aims to evaluate the budget impact for the Spanish National Health System (SNHS) of treating ID in reduced LVEF CHF with FCM compared to non-iron treatment. Methods: We simulated a hypothetical cohort of 1000 CHF patients with ID and reduced LVEF based on the Spanish population characteristics. A decision-analytic model was also built using the data from the largest FCM clinical trial (CONFIRM-HF) that lasted for a year. We considered the use of healthcare resources from a national prospective study. A deterministic sensitivity analysis was carried out varying the corresponding baseline data by ±25%. Results: The cost of treating the simulated population with FCM was €2, 570, 914, while that of the non‐iron treatment was €3, 105, 711, which corresponds to a cost saving of €534, 797 per 1, 000 patients in one year. Cost savings were mainly due to a decrease in the number of hospitalizations. All sensitivity analysis showed cost savings for the SNHS. Conclusions: FCM results in an annual cost saving of €534.80 per patient, and would thus be expected to reduce the economic burden of CHF in Spain.